2020
DOI: 10.1088/1757-899x/852/1/012083
|View full text |Cite
|
Sign up to set email alerts
|

Tool Wear Analysis of Coated Carbide Tools on Cutting Force in Machining Process of AISI 4140 Steel

Abstract: In manufacturing industries specifically in metal machining, the use of the cutting tool is important to consider. The use of the cutting tool has not been used optimally, as well as cutting parameters. In the cutting process, the wear of the cutting tool and cutting force has a very close relationship. This research was carried out to analyze the wear of coated carbide cutting tool and cutting forces produced in turning AISI 4140 steel workpieces. This study was conducted with a variation of five cutting spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The force signal is the preferred signal for online tool wear monitoring as it best reflects changes in tool condition. Lubis.et al [20] found that tool wear causes changes in cutting forces. The cutting force signal is more sensitive to tool wear than other signals.…”
Section: Signal Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The force signal is the preferred signal for online tool wear monitoring as it best reflects changes in tool condition. Lubis.et al [20] found that tool wear causes changes in cutting forces. The cutting force signal is more sensitive to tool wear than other signals.…”
Section: Signal Acquisitionmentioning
confidence: 99%
“…Event data usually includes discrete events happening on the target machine based on manual entries, for example, manual installation, scheduled maintenance, abrupt breakdown, etc. [16] Monitoring and prediction data usually adopt signals related to tool wear collected by sensors, such as sound signal [17][18][19],cutting force signal [20] etc. Through the analysis and processing of the signal, the relevant characteristics are extracted, and then the established model [21][22][23][24] is used to identify the wear state, and the prediction results of the tool wear state and RUL are obtained, and the results are fed back to the machine tool.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, machinery, parts and apparatus, agricultural vehicles, a number of products used in the defense areas and the petroleum and derivatives industry are various area of usage of AISI 4140 steel. Machining operations are performed on the material with various methods since it has a very wide area of use (Şahinoğlu and Rafighi (2020), Gürbüz and Gönülaçar (2020), Schwalm et al (2020) and Lubis et al (2020)).…”
Section: Introductionmentioning
confidence: 99%